2021
DOI: 10.1002/iub.2450
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 10 exerts antitumor effects on cervical cancer via a novel microRNA‐223/TXNIP/Wnt/β‐catenin pathway

Abstract: Dysfunction of histone deacetylase 10 (HDAC10) has been suggested in the carcinogenesis of cervical cancer (CC). However, its association with micro-RNAs (miRNAs) in CC remains exclusive. Hence, this study aims to probe the role of HDAC10 in regulating CC cell proliferation, migration, and invasion and its correlation with the screened-out miRNA target. Microarray analysis and RT-qPCR revealed that HDAC10 expressed poorly in CC cells relative to human immortalized endocervical cells (End1/E6E7). Moreover, HDAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Afuresertib, ipatasertib and MK-2206 are key antitumor drugs as they potentially inhibit AKT kinase ( 41 ). Elevated levels of TXNIP expression can suppress the activity of the Wnt/β-catenin and PI3K/AKT/mTOR signaling pathways ( 67 69 ). This mechanism may therefore be related to enhanced drug sensitivity, but further evaluation is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Afuresertib, ipatasertib and MK-2206 are key antitumor drugs as they potentially inhibit AKT kinase ( 41 ). Elevated levels of TXNIP expression can suppress the activity of the Wnt/β-catenin and PI3K/AKT/mTOR signaling pathways ( 67 69 ). This mechanism may therefore be related to enhanced drug sensitivity, but further evaluation is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, understanding and figuring out the influence of HDACs on the cervical cancer progression would contribute to develop the potential preferable therapeutic treatment. Numerous evidences in previous studies reported that HDAC10 was expressed at different levels in diverse kinds of cancers [ 34 ]. HDAC10 was reported to negatively regulate the progression of cervical cancer by miR-1908 [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A remarkable study has shown that pan-HDAC inhibitor promotes breast cancer metastasis due to the inhibition of HDAC4 [ 113 ]. Another study has revealed the tumor suppressive role of HDAC10 in cervical cancer [ 114 ].…”
Section: Cancermentioning
confidence: 99%